2023
DOI: 10.3354/esr01268
|View full text |Cite
|
Sign up to set email alerts
|

Post-fledging distribution of ’ua’u (Hawaiian petrel Pterodroma sandwichensis) from Kaua’i, Hawai’i and effectiveness of rehabilitation

Abstract: The ‘ua’u (Hawaiian petrel Pterodroma sandwichensis) is an Endangered seabird endemic to the Hawaiian Islands. The at-sea distribution of this species is an under-studied aspect of its ecology. We tracked 10 petrels fledging from the island of Kaua’i to their first wintering grounds, an area which has not previously been described. We also compare birds fledging naturally from their burrows with birds that were grounded by light attraction, rehabilitated, and released. All fledglings travelled over 2000 km sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Lineages originating in Southeast Asia primarily reached the Pacific Islands through bird migration along the West Pacific Flyway [ 39 ]. For instance, investigations have revealed that fledglings of the Hawaiian petrel ( Pterodroma sandwichensis ) traverse southwestward to Melanesia and then turn northwest, reaching the Philippines and Taiwan, in China, in winter, ultimately returning to Hawaii for breeding in summer [ 40 ]. Furthermore, certain avian species, such as the ruddy turnstone ( Arenaria interpres ), red knot ( Calidris canutus ), and curlew sandpiper ( Calidris ferruginea ), undertake migratory journeys from China to New Zealand [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lineages originating in Southeast Asia primarily reached the Pacific Islands through bird migration along the West Pacific Flyway [ 39 ]. For instance, investigations have revealed that fledglings of the Hawaiian petrel ( Pterodroma sandwichensis ) traverse southwestward to Melanesia and then turn northwest, reaching the Philippines and Taiwan, in China, in winter, ultimately returning to Hawaii for breeding in summer [ 40 ]. Furthermore, certain avian species, such as the ruddy turnstone ( Arenaria interpres ), red knot ( Calidris canutus ), and curlew sandpiper ( Calidris ferruginea ), undertake migratory journeys from China to New Zealand [ 41 ].…”
Section: Discussionmentioning
confidence: 99%